The good, the bad, and the uncertain: state harm, the aftermath of exoneration, and compensation for the wrongly convicted - Madrigal, Andrew J. (Critical criminology, 2022)
As the number of exonerations in the USA continues to grow, so does the need to address post-release challenges faced by those who experience wrongful conviction. Research has highlighted many challenges faced by exonerees after release, yet compensation and reentry services are often lacking. In this paper, we provide a content analysis of existing exoneree-compensation statutes. Using Westervelt and Cook’s (Crime Law Soc Change 53(3):259-275, 2010) conceptualization of the wrongly convicted as victims of state harm, we describe current policies, organizing our findings around what is good, what is bad, and what is left uncertain. We argue that during the reentry period, a time filled with extreme uncertainty, many existing laws remain inadequate and/or unclear. Rather than providing stability, existing laws often create an additional layer of uncertainty for exonerees seeking compensation and other reentry assistance as they try to rebuild their lives.